2013
DOI: 10.1093/jscr/rjs047
|View full text |Cite
|
Sign up to set email alerts
|

A case of metaplastic breast cancer in a man

Abstract: Metaplastic breast cancers (MPBCs) represent <1% of breast cancers. Reports of MPBC in men are limited to case reports. We report a case of MPBC with pulmonary metastasis occurring in a 59-year-old man who initially presented with a presumed breast abscess. Histology from the breast lesion revealed a poorly differentiated carcinoma and a computed tomography scan showed an ulcerative right-sided breast mass and an area of scarring in the apex of the left lung. The breast lesion and the lung lesion were resected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…1 In addition, the lung is the most common organ of metastasis during the progression of MSCCB. [14][15][16] Recently, some studies showed that a patient with a history of breast cancer has a higher risk of developing other primary non-mammary cancer types, particularly in the lung. [17][18][19] When a lung nodule is found in a patient with a history of MSCCB, it can be difficult to diagnose definitively whether it is metastatic MSCCB or primary lung squamous cell carcinoma (LUSC).…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, the lung is the most common organ of metastasis during the progression of MSCCB. [14][15][16] Recently, some studies showed that a patient with a history of breast cancer has a higher risk of developing other primary non-mammary cancer types, particularly in the lung. [17][18][19] When a lung nodule is found in a patient with a history of MSCCB, it can be difficult to diagnose definitively whether it is metastatic MSCCB or primary lung squamous cell carcinoma (LUSC).…”
Section: Introductionmentioning
confidence: 99%
“…MBC accounts for less than 1% of breast cancer diagnoses and is extremely rare in males. We found only 5 cases of male MBC reported in the literature[ 1 - 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It constitutes approximately 5% of all breast cancers in men, compared with 1%-2% in women with breast carcinomas (24). Non-Hodgkin lymphoma, malignant melanoma, oncocytic carcinoma, secretory carcinoma, mucinous carcinoma, and metaplastic carcinoma have been rarely reported (1,18,20,(24)(25)(26)(27)(28). Metastatic involvement of male breasts with SCC and melanoma are also identified sporadically (26).…”
Section: Discussionmentioning
confidence: 99%